When Women Work at the Iron Cage: Gendered Perceptions on Workplace Justice - Hsieh, Ming-Li (Women & criminal justice, 2020)
Given the increase in the percentage of female employees in correctional institutions, it is important to note that female correctional officers often hold different values relative to justice and fairness than their male counterparts. The current study attempts to understand whether gender differences would affect correctional officers’ perceptions of organizational justice in Ghanaian prisons. Results indicate that women and men did differ in how they perceive distributive and procedural justice under a multivariate model controlling for demographics and job-related attitudes. This implies that the job model hypothesis might better explain female officers’ perceptions of workplace justice than a gender model hypothesis in Ghanaian corrections.